PENGENTASAN PATOLOGI SOSIAL SEASONAL UNEMPLOYMENT DAN PENGUATAN SEKTOR-SEKTOR DI PERDESAAN DANASARI SEBAGAI USAHA MENCIPTAKAN PEMBANGUNAN BERKELANJUTAN NASIONAL - Agus Mauluddin (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Seasonal unemployment is one type of unemployment caused by certain seasons in the countryside. This type of unemployment is one of the social pathologies that have direct implications for the people in Danasari Rural. The socio-spatial community of the village has an agricultural sector which is a lot of choice. When seasonal unemployment is alleviated and with the existence of the agricultural sector, it should be the initial foundation for the creation of sustainable development. Sustainable development departing from rural areas. Village, in this case village food becomes National food. This means that villages are able to supply food for their regions and are able to provide sufficient food for national food needs. At a certain point National food can compete in the Global Level; Global food supply and no more dependence on food supplies from outside countries.